2014
DOI: 10.1007/s10444-014-9370-3
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of Wachspress coordinates: from polygons to curved domains

Abstract: Given a smooth, strictly convex planar domain, we investigate point-wise convergence of the sequence of Wachspress coordinates defined over finer and finer inscribed polygonal approximations of the domain. Based on a relation between the discrete Wachspress case and the limit smooth case given by the Wachspress kernel defined by Warren et al., we show that the corresponding sequences of Wachspress interpolants and mappings converge as O(h 2 ) for a sampling step size h of the boundary curve of the domain as h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…It is easy to see that (19) reproduces exactly constant and linear functions. In contrary to solutions computed with the finite element method, (19) can be evaluated pointwise without the need to mesh the computational domain.…”
Section: Analytical Derivationsmentioning
confidence: 94%
See 3 more Smart Citations
“…It is easy to see that (19) reproduces exactly constant and linear functions. In contrary to solutions computed with the finite element method, (19) can be evaluated pointwise without the need to mesh the computational domain.…”
Section: Analytical Derivationsmentioning
confidence: 94%
“…While the approximations delivered by (19) are good in these examples, it may not always produce a sufficiently accurate approximation. For example, the approximation error for the ring domain (see Fig.…”
Section: Let Us Test Interpolation Scheme (19) On the Fundamental Solmentioning
confidence: 95%
See 2 more Smart Citations
“…Considering denser and denser polygons inscribed into a smooth domain leads to a (convergent) series of barycentric coordinates. This limit process was recently investigated in the case of Wachspress coordinates in Kosinka and Bartoň (2015). It was shown that in the limit, as the number of vertices of the polygon approaches infinity, one obtains the Wachspress kernel Warren et al (2007) introduced by Warren et al, and that the convergence rate is quadratic.…”
Section: Introductionmentioning
confidence: 99%